Promoting the use of home-mixed supplements as alternatives to commercial supplements in smallholder beef production systems in the subhumid region of Zimbabwe - Chakoma, Irenie; Manyawu, Godfrey J.; Gwiriri, Lovemore C.; Moyo, Siboniso; Dube, Sikhalazo; Imbayarwo-Chikosi, V.E.; Halimani, T.E.; Chakoma, C.; Maasdorp, B.V.; Buwu, V. (National Inquiry Services Center, 2016)
The economic and performance effect of supplementing smallholder cattle by substituting commercial feed with iso-nitrogenous and iso-energetic diets based on alternative protein sources was investigated in two trials. In trial 1, three diets (commercial concentrate, commercial concentrate partially substituted with mucuna, and commercial concentrate partially substituted with lablab–cowpea) compared with veld grass were allocated to 12 cattle in a complete randomised block design. In trial 2, a double complete randomised block design with 40 cattle assigned to four forage legume-based diets, a poultry-based diet and a commercial beef concentrate was carried out. Diets were offered at 1.5% of body weight daily over 56 d. Average daily weight gain (ADWG) was measured weekly in trial 1 and fortnightly in trial 2. In trial 1, ADWG was significantly (p < 0.05) higher for animals on supplements compared with non-supplemented cattle. In trial 2, ADWG was significantly highest on the groundnut stover-based diet and least on the poultry litter diet. Supplementation had a positive effect on ADWG and economic performance of smallholder beef cattle. Substitution of commercial concentrates with alternative protein sources reduced diet costs and significantly improved gross margins.